Metodologia de avaliação de risco de acidentes na colheita florestal - Bermudes, Wanderson Lyrio (2018)
In the forest harvest, regardless of the degree of mechanization, human labor will always be present, which requires adequate planning to reduce the rates of occupational accidents and diseases that have accumulated in Brazil. In the period from 2007 to 2016, there were a total of 18,934 records in planted forest activities in the country. Despite a variety of risk assessment techniques available in the literature, the forest sector, especially the forest harvest, lacks a proper process that can carry out this planning and is easy to understand and apply. This work aims to develop a Forest Harvest Risk Assessment Process (PARCF) in order to provide and facilitate adequate management of the risks present in the development of forest activities, and also indicates the establishment of indicators to measure and monitor the safety and health at work. The PARCF was based on NBR ISO 31000: 2018 and other assessment techniques described in NBR ISO 31010: 2012, based on the identification, analysis and evaluation of the risks of accidents and occupational diseases in two empirical studies characterized as action research, in addition to including employee participation through a specific questionnaire applied to a pilot sample. It included the analysis of meteorological, forest, human and social factors, organizational, operational and economic of the forest harvest, legal aspects derived from the Regulatory Norms of the Ministry of Labor in Brazil, and employs a matrix as a support tool to assess the level of risk . PARCF has been established for its application to pre-interpret the influencing factors of the forest harvest, the stages of the task, its risks, sources, causes, consequences, applicable legislation and level of risk, in order to adopt measures to ensure job. The PARCF can be applied in the planning prior to the forest harvesting activity or used in the work fronts as a guideline for the organizations, to implement more appropriate control actions, as presented in the case studies applied in a forestry development company with semimechanized activity and in a pulp industry in mechanized harvesting activities, which used a process of own risk assessment that when compared to PARCF demonstrated inefficiency in the identification of management controls. Reactive and proactive indicators were also established to measure and monitor health and safety performance in the forest harvest. The creation and application of a process of risk assessment in the forest harvest favor the worker and the organization in the reduction of accidents and, associated to methods of measurement and monitoring of the health and safety performance of the work, can contribute to the improvement of the method management of this important segment.